Brain abscess due to Streptococcus intermedius secondary to mastoiditis in a child - DAĞÇINAR, ADNAN; KEPENEKLİ KADAYİFCİ, EDA; AKBULUT, FATİH; YAKUT, NURHAYAT (SPRINGER INTERNATIONAL PUBLISHING AG, 2015)
Background: Brain abscess is a rare but serious, life-threatening infection in children. It may arise from parameningeal infections such as otitis media, sinusitis and mastoiditis. Case description: A ten-year-old boy with the diagnosis of glycogen-storage disease and obesity was admitted to the emergency room with complaints of vomiting, decreased level of consciousness, imbalance on walking. On neurological examination, the patient was ataxic. His cranial magnetic resonance imaging (MRI) examination showed mastoiditis on the right side and 39 x 34 mm abscess formation with surrounding edema on the right cerebellar hemisphere. The patient underwent surgery to drain the abscess, microbiological samples were obtained and empirical antibiotic treatment with vancomycin and piperacillin-tazobactam were started. Postoperative cranial MRI examination showed that the lesion regressed 10 x 10 mm with a reduction in the edema. On the second week of the treatment, the antibiotics were switched to vancomycin and meropenem because of the relapsing fever. The therapy was continued for 6 weeks. A final MRI (after completing antibiotherapy) showed resolution of the cerebellar abscess. The child's clinical condition improved and he was discharged without any sequelae. Discussion and evaluation: Children with congenital heart disease and an immonocompromised state are particularly at risk. Streptococcus intermedius is usually a commensal microorganism in the normal flora of the mouth which can cause brain abscess rarely in children. Brain abscess induced mortality rates are still relatively high, even with the advancement of imaging technologies, the combination of surgical drainage and antimicrobial therapy. Conclusion: This case is one of the few reported cases of cerebellar abscess caused by S. intermedius in an immunocompetent child, due to its low virulence, a rare occurence and timely management resulting in fully healed.
Keywords: Brain abscess; Streptococcus intermedius; Child; Mastoiditis; CLINICAL-FEATURES; MANAGEMENT